Employability Skills Developed through Internship Experiences in PLN Customer Service Units - Aryan Agus Pratama; Fatimah Akbal (Business Research and Administration Innovation, 2026)
The development of the contemporary labor market demands that university graduates possess not only technical skills but also interpersonal and professional competencies that support work readiness. In this context, internship programs serve as a critical vehicle for developing employability skills through authentic work experiences. This study aims to identify and describe the employability skills developed through the internship experiences of Business Administration students at the Customer Service Unit (ULP) of PT PLN (Persero). A descriptive qualitative approach was employed, with data collected from student internship reports, in-depth interviews, and documentation. Data were analyzed using Qualitative Content Analysis (QCA) through the processes of open coding, categorization, and theme abstraction. The findings reveal that the employability skills developed encompass two principal dimensions: hard employability skills and soft employability skills. Soft employability skills developed more prominently than hard employability skills, attributable to the nature of work in the Customer Service Unit, which demands intensive customer interaction and coordination within an organizational setting. The combination of these skills also constitutes transferable competencies that contribute to long-term employability. This study yields implications for curriculum development and internship programs oriented toward the integration of technical and non-technical skills in preparing graduates for the professional world.